2004
DOI: 10.1055/s-2004-825904
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Postprandial Hyperglycemia in Patients with Type 2 Diabetes Reduces NF-κB Activation in PBMCs

Abstract: Reduction of postprandial glucose peak levels by acarbose reduces postprandial mononuclear NF-kappaB activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 24 publications
1
30
0
5
Order By: Relevance
“…However, the effect of the postprandial state, particularly postprandial hyperglycaemia, on CVD is still a matter of debate [21,22]; studies show that postprandial hyperglycaemia is accompanied by an increase of both oxidative stress and inflammatory markers [11][12][13][14][15]. This evidence is supported by findings showing an increase in vivo, during postprandial hyperglycaemia, of both protein kinase C and nuclear factor kappa B, two factors which regulate the generation of oxidative stress and inflammation [23,24].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the effect of the postprandial state, particularly postprandial hyperglycaemia, on CVD is still a matter of debate [21,22]; studies show that postprandial hyperglycaemia is accompanied by an increase of both oxidative stress and inflammatory markers [11][12][13][14][15]. This evidence is supported by findings showing an increase in vivo, during postprandial hyperglycaemia, of both protein kinase C and nuclear factor kappa B, two factors which regulate the generation of oxidative stress and inflammation [23,24].…”
Section: Discussionmentioning
confidence: 97%
“…However, the possibility that postprandial hyperglycaemia increases oxidative stress and inflammation in healthy subjects has previously been reported [12,13]. Furthermore, evidence showing that modulation of postprandial hyperglycaemia by diet or an insulin analogue in type 2 diabetes [25][26][27], and by pramlintide [28] in type 1 diabetes, is accompanied by a significant decrease of oxidative stress, while nuclear factor kappa B activation is decreased when controlling postprandial hyperglycaemia by acarbose [24], convincingly suggests that the effect of S21403 on postprandial oxidative stress and inflammation is related to its ability to reduce postprandial hyperglycaemia.…”
Section: Discussionmentioning
confidence: 98%
“…42 High dietary fructose consumption (60% wt/wt in chow) also induces a stress response in liver and other tissues in tandem with insulin resistance and lipid metabolic dysregulation. 43 Our results indicate that fructose ingestion, in the absence of insulin resistance, is also capable of inducing a stress response in liver by increasing NF-B activity.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term studies also have demonstrated benefits on postprandial lipemia and inflammatory markers. 63,64 One diabetes prevention study involving the ␣-glucosidase inhibitor acarbose demonstrated an impressive 91% relative risk reduction in MI compared with the control group, although the validity of these findings is challenged by the extremely low number of MI events evaluated (12 versus 1) and 24% attrition of study treatment. 65 These agents should be considered in patients with mild hyperglycemia, particularly when other drug options are limited because of preexisting contraindications.…”
Section: Inzucchi and Mcguire Diabetes Drugs: Incretin-based Therapy mentioning
confidence: 99%